Participation after Stroke and Traumatic Brain Injury: Results of a Pilot Study in Outpatient Neurorehabilitation in Vorarlberg - Pöppl, Dominik; Marheineke, Judith; Deck, Ruth (Neurology International Open, 2017)
Objective A multicentric study has reported on the sustained effects of outpatient neurorehabilitation in Germany. Different to Germany, the biopsychosocial model of disability, as described in the International Classification of Functioning, Disability and Health (published by the World Health Organization), is not incorporated into Austrian law. There is a need for objective measurement instruments for routine outcome evaluation of outpatient neurorehabilitation in Austria. The present examines the extent to which the instruments used for the German multicentric study are applicable in the Austrian rehabilitation context and if there are similar rehabilitation effects over time.Method In a multicentric observational study, patients of 4 Austrian outpatient neurorehabilitation centers for stroke or traumatic brain injury were asked to fill in a questionnaire. This was carried out 4 times throughout the program: on admission and discharge as well as on month 4 and 12 post rehabilitation. Additionally, clinical experts were asked to rate the patients’ status at admission and discharge.Results and conclusions The results of 4 outpatient neurorehabilitation centers in Vorarlberg (Austria) suggest that the used measurement instruments are reasonable for the evaluation of outpatient neurorehabilitation in Austria, based on the ultimate goal “participation and self-determined conduct of life”. For routine outcome evaluation, fewer instruments should be used and adjustments should be made while assessing more severely affected patients.
Keywords: traumatic brain injury; measurement of outcomes; stroke; outpatient neurological rehabilitation